Proceedings of the 19th International Conference on World Wide Web 2010
DOI: 10.1145/1772690.1772770
|View full text |Cite
|
Sign up to set email alerts
|

Diversifying web search results

Abstract: Result diversity is a topic of great importance as more facets of queries are discovered and users expect to find their desired facets in the first page of the results. However, the underlying questions of how 'diversity' interplays with 'quality' and when preference should be given to one or both are not well-understood. In this work, we model the problem as expectation maximization and study the challenges of estimating the model parameters and reaching an equilibrium. One model parameter, for example, is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 20 publications
0
77
0
Order By: Relevance
“…23 We first investigated creating a set of fixed ambiguous topics using Wikipedia's disambiguation pages, which indicate concepts or topics that may have multiple meanings. This methodology was used in previous evaluation schemes in the literature [14,15]. However, after an initial analysis of the worker's feedback, we found that workers were sometimes unfamiliar with the selected ambiguous topics, and were as a consequence unable to provide consistent relevance judgments.…”
Section: Evaluation Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…23 We first investigated creating a set of fixed ambiguous topics using Wikipedia's disambiguation pages, which indicate concepts or topics that may have multiple meanings. This methodology was used in previous evaluation schemes in the literature [14,15]. However, after an initial analysis of the worker's feedback, we found that workers were sometimes unfamiliar with the selected ambiguous topics, and were as a consequence unable to provide consistent relevance judgments.…”
Section: Evaluation Frameworkmentioning
confidence: 99%
“…For instance, if is an Open Directory Project (ODP) category as in [1,14], we may estimate ( | ) by a text classification method as the probability that document belongs to class . Other estimation approaches can be applied for query aspects of a different nature.…”
Section: Personalized Xquadmentioning
confidence: 99%
See 1 more Smart Citation
“…A greedy algorithm is used for ranking search results such that relevance is maximized while variance is minimized. Rafiei et al [29], introduce a similar framework based on Portfolio Theory for reranking Web search results. The problem of result diversification is also investigated in the area of structured data queries.…”
Section: B Diversifying Review Rankingsmentioning
confidence: 99%
“…Finally, they proposed an evaluation methodology to characterize the objectives and the underlying axioms. Rafiei et al [12] modeled the diversity problem as expectation maximization and presented algorithms to estimate the optimization parameters. In [4], documents are selected sequentially according to relevance.…”
Section: Introductionmentioning
confidence: 99%